2006
DOI: 10.1182/blood.v108.11.2566.2566
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Strategies of MSC Isolation Revels Advantage To Expand MSC Directly from Purified CD105+ and CD271+ Cells.

Abstract: The potential for multilineage differentiation together with the ability to expand in cultures are the reasons why Mesenchymal Stem Cells (MSC) are considered to be the population of stem cells for potential treatment for variety of disorders (e. g. Osteogenesis Imperfecta, Myocardium Infarction, GvHD). MSC are isolated from the bone marrow mononuclear cells (MNC) based on their adhesive properties. There have been few attempts to isolate MSC directly based on the expression of selected surface antigens, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous work investigating the functionality of CD271-enriched BM MSCs, in terms of morphology, immunophenotype and tri-lineage potential, has employed research-grade anti-CD271 microbeads [ 17 , 24 , 46 ]. Here, we assessed the suitability of clinical-grade CD271 microbeads to isolate functionally competent MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work investigating the functionality of CD271-enriched BM MSCs, in terms of morphology, immunophenotype and tri-lineage potential, has employed research-grade anti-CD271 microbeads [ 17 , 24 , 46 ]. Here, we assessed the suitability of clinical-grade CD271 microbeads to isolate functionally competent MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Jarocha et al comparison of different strategies of MSCs isolation revealed advantage to expand MSC directly from purified CD105 + and CD271 + cells. 32 Tregs were characterized in bone marrow samples by measuring positive CD25 expression on gated CD4+ cells. Although the expression of FoxP3, a member of the forkhead/winged-helix family of transcriptional factors, is considered an optimal marker for Tregs.…”
Section: Discussionmentioning
confidence: 99%